Teacher competence and students’ career interest: The mediating role of 21st-century skills in automotive vocational education - Bambang Sudarsono; Nanda Priya Pratama; Estrella T. Arroyo (ADGVI & Graduate School of Universitas Negeri Yogyakarta, 2026)
This study examined the relationships among teachers’ Technological Pedagogical Content Knowledge (TPACK), professional competence, students’ 21st-century skills, and career interest in automotive vocational education. Using a quantitative explanatory survey design, data were collected from 174 students enrolled in nine vocational schools in Indonesia. The proposed model was tested using Partial Least Squares Structural Equation Modeling (PLS-SEM) to evaluate direct and indirect relationships among the variables. The findings revealed that both TPACK (β = 0.43, p < 0.001) and teachers’ professional competence (β = 0.35, p < 0.001) significantly enhanced students’ 21st-century skills. However, neither TPACK (β = 0.06, p = 0.47) nor professional competence (β = 0.08, p = 0.34) had a significant direct effect on students’ career interest. In contrast, 21st-century skills exerted a strong positive influence on career interest (β = 0.48, p < 0.001). Mediation analysis further demonstrated that 21st-century skills serve as a significant intermediary mechanism linking teacher competence to students’ career aspirations. The results suggest that teacher competence contributes to career development primarily through fostering transferable competencies such as critical thinking, communication, collaboration, creativity, and digital literacy. The study’s novelty lies in integrating TPACK, teachers’ professional competence, 21st-century skills, and Social Cognitive Career Theory (SCCT) into a unified explanatory model. Unlike previous studies that examined these variables separately, this research identifies 21st-century skills as the key pathway through which teacher competence influences career interest. The findings offer practical implications for vocational education by highlighting the importance of strengthening teacher competence, technology-integrated pedagogy, and the systematic integration of 21st-century skills into vocational curricula to better prepare students for future workforce demands.